The Brons-Mulié analysis as a decision-making tool for preoperative surgical simulation in orthognatic surgery - Böttger, Sebastian; Nowak, Yannick; Windhorst, Anita Cornelia; Klaus, Katharina; Ruf, Sabine; Bäcker, Christina; Schraml, Eva May; Danevitch, Nina; Mulié, Rob; Howaldt, Hans-Peter; Attia, Sameh (Frontiers in Oral Health, 2025)
ObjectivesSufficient preoperative planning represents an essential component for the success of orthognathic surgery. Using various analysis methods, dysmorphic areas can be reliably identified and addressed during the planning procedure.MethodsBrons-Mulié analysis was used to examine profile photographs before and after orthognathic surgery. The attainment of normal values was interpreted as the achievement of facial harmony of the various facial proportions. By comparing the pre- and postoperative analysis, a control of the outcome quality of the orthognathic procedures was performed.ResultsIn a total of 160 patients aged 13 to 61 years, the preoperative analysis could be compared with the postoperative Brons-Mulié analysis. Postoperative, facial harmony was found for the vertical dimension in 99 cases (62%), for the upper lip dimension in 95 cases (59%), for the lower lip dimension in 138 cases (86%), and for the chin dimension in 118 cases (74%). This corresponded to an improvement of 20% in the vertical dimension, of 27% in the area of the lower lip and of 6% in the area of the chin. The upper lip area showed a slight deterioration of 7%.ConclusionDespite preoperative planning of orthognathic surgery with Brons-Mulié analysis, postoperative results show an overall improvement but not perfection. Even by applying the method, it remains a challenge to achieve perfect facial harmony.